Life in Between Identity and Profession of Waria in Semarang - Devitasari, Rafaela Tiara; Hanjani, Vania Pramudita (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
Waria are often referred to as marginalised people who are subject to double standards in society and need to be normalised. This is evidenced by the fact that those who work in the entertainment sector are entirely accepted and have many enthusiasts even though in their daily lives they receive unpleasant treatment. The phenomenon of transvestites as an alternative form of entertainment raises new perceptions about the economic dynamics taking place in Semarang. The emergence of waria in the hustle and bustle of the entertainment world creates its own buzz because of the acceptance of various groups of people who use their services. Aided by Pierre Bourdieu's review of Capital Theory, it provides a bright spot in interpreting the position of waria in fulfilling their economic needs. Emerging as a famous entertainment actor certainly requires capital from various aspects. This capital further elaborates on the process of waria exertion in their career, which has its own impact on society's perception. Using the perspective of economic anthropology, it results in a comparative construction of the economic dynamics of waria, which shows significant differences in expressing themselves between their identity and the demands of their profession.Â  The dynamics of waria, supported by many factors, make them engage in entertainment specialisation not only because it is their expertise but also because it is the only place that can accept their existence.
Keywords: Waria, Identity, Profession, Entertainment, Capital